G530(P) Loading doses of IV aminophylline: serum concentrations and clinical outcomes. (27th April 2016) - Cooney, L; Hawcutt, D; Sinha, I; Lilley, A; McBride, A; Lansdale, R
Abstract : Background: Intravenous aminophylline is a second line treatment for children suffering an acute exacerbation of asthma. A loading dose of 5 mg/kg is recommended for children who do not take oral theophylline in order to achieve a target therapeutic range of 10–20 mg/l. This dose was calculated based on theoretical pharmacokinetic data. This study aims to assess whether a 5 mg/kg loading dose achieves therapeutic levels, and report on the clinical outcomes using routine therapeutic drug monitoring (TDM) data. Method: A prospective audit analysing the serum theophylline levels and outcomes of children who receive a 5mg/kg loading dose for an acute exacerbation of asthma between August 2014 and October 2015. Results: Of 29 admissions requiring IV aminophylline, 16 children were on maintenance doses (and therefore did not receive loading doses). Thirteen children were therefore included. All children received 5mg/kg IV aminophylline. Twelve TDM samples were taken ≤1 h post dose (8 were ≤30 min). One child achieved serum theophylline levels between 10–20mg/l, 12 children had levels <10mg/l and no children had levels >20mg/l. The average theophylline level achieved was 7.9 ± 0.5mg/l. Mean length of stay was 4.6 ± 3.7 days, mean days until in child was in room air was 2.0 ± 0.6, and mean days until managed on only 5 puffs inhaled salbutamol 4 hly was 3.1 ± 0.4 days. One child require PICU admission. The adverse effects of cardiac arrhythmias, nausea, hypokalaemia and hypoalbuminaemia were seen in 0, 2, 5 and 3 children respectively. Conclusion: A 5mg/kg loading dose fails to achieve a serum level of >10mg/l. The resolution of symptoms in children who require intravenous aminophylline is slow, and adverse effects are noted in this population. Research to determine the optimal loading dose of aminophylline is required.